Endocrown Feasibility for Primary Molars: A Finite Element Study - Abduljabar, Aeshah Hassan; Iskander, Ahmad Waleed; Elfezary, Mohamed Taha; Wakwak, Mohamed AboElkasem Ahmed; Bathabt, Wafa Abdullah; Souror, Yasser R. (European Journal of Dentistry, 2023)
Objective To study the possibility of using pediatric endocrowns to restore the second primary molar using three-dimensional (3D) finite element analysis.Design A 3D finite element model was built for a pediatric mandibular molar, starting with laser scanning a naturally extracted tooth. The access cavity had an elliptic shape with 6 mm width, 4 mm height, and 2 mm depth with a wall taper angle of 5 degrees.Two materials (Zr and E-max) were tested for the endocrown and two cementing materials (glass ionomer and resin cement) with 20 to 40 μm thickness. Twelve case studies were reported within this research as the applied load of 330 N was tested with three angulations vertical, oblique at 45 degrees, and laterally.Results Twelve linear static stress analyses were performed. The resultant stresses and deformations' distribution patterns did not alter much, and values were within the threshold of physiological tolerance. Deformations were negligibly changed with changing endocrown and cement materials. In contrast, endocrown stresses indicated zirconia endocrown would have a long lifetime, while E-max one will have a relatively short lifetime.Conclusions Analysis results indicated that bone was negligibly affected by changing endocrowns and cementing materials. Both tested endocrown materials can be used safely. Zirconia endocrowns may have a much longer lifetime than E-max.
Keywords: primary molar; endocrown; zirconia; E-max; finite analysis